GIG ECONOMY SHAKEUP : HOW IT’S RESHAPING JOBS, PAYCHECKS AND THE WORLD’S ECONOMY - Budoyo, Yoga Kassapa; Suyanto, Suyanto (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
The gig economy has arisen as a dynamic yet intricate factor in worldwide labor markets, providing workers with more flexibility but also posing substantial challenges concerning job security, wages, and legal protections. This research uses a bibliometric review of 980 academic articles and investigates significant elements influencing the gig economy, such as actual salaries, inflation rates, joblessness, data utilization, and gender interactions. Five primary groupings were detected, each illustrating the intricate connection among these variables. The results show that although the gig economy offers flexible work options, it also worsens problems like income inequality, exploitation, and gender disparities. Utilizing data-driven strategies and organizing labor movements are becoming more crucial in addressing these issues, providing gig workers with resources to enhance their work environments. This article discusses the economic and social impacts of the gig economy, and suggests policy suggestions to promote a fairer and more comprehensive job market for all employees.